2008
DOI: 10.1080/13586840802493043
|View full text |Cite
|
Sign up to set email alerts
|

Listening to Difference in the Teaching of ‘English’: Insights from Internationally Educated Teachers

Abstract: More than 25 years ago, Ferguson first wrote about 'one of the most significant linguistic phenomena of our time, the incredible spread of English as a global language' (1992, xiii) -an historically unprecedented phenomenon in terms of its scale (see also Fishman 1998). English has the second largest number of mother tongue speakers worldwide; there are also large numbers of people around the globe who speak localised forms of English, speak English as a lingua franca and also learn English as a foreign or add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Since most IETs are new immigrants coming from non-Western societies, their language and cultural differences are often perceived as knowledge deficiency by Canadian institutions, both schools and universities. Similarly, Walsh (2008) noted that IETs encountered discourses that IETs are "not good enough English speakers" (p. 402) to teach in Canadian schools. Further, Cho's (2010) analysis revealed that IETs' cultural wealth and their ability to speak multiple languages are not always valued as an asset but instead "accent" is perceived as deficiency in terms of teaching qualifications.…”
Section: Overview Of Existing Researchmentioning
confidence: 99%
“…Since most IETs are new immigrants coming from non-Western societies, their language and cultural differences are often perceived as knowledge deficiency by Canadian institutions, both schools and universities. Similarly, Walsh (2008) noted that IETs encountered discourses that IETs are "not good enough English speakers" (p. 402) to teach in Canadian schools. Further, Cho's (2010) analysis revealed that IETs' cultural wealth and their ability to speak multiple languages are not always valued as an asset but instead "accent" is perceived as deficiency in terms of teaching qualifications.…”
Section: Overview Of Existing Researchmentioning
confidence: 99%
“…6 Our work together involved storytelling and artistic response, a process whereby we wrote individually at each meeting about a teaching or immigration/integration experience. When a person shared her story (usually one per meeting), we responded to it through various arts media, including watercolor paint, clay, fabric, blocks, and so on (see Walsh, 2006Walsh, , 2008Walsh & Brigham, 2007). Our artful responses were a way of listening to one another through the research process.…”
mentioning
confidence: 99%
“…However, international research indicates accents and vocabulary that are not local are perceived as a barrier to student learning by school-hiring staff. In contrast, findings indicate that although children may struggle initially to understand a new accent or word, but will find it easier to understand after hearing it again and then no longer struggle with comprehension (Sharplin, 2009;Walsh, 2008). These findings could allay the fears that students cannot learn from multilingual OTTs.…”
Section: Culture Shockmentioning
confidence: 88%
“…She stated that potential employers expected her to struggle when speaking English in spite of it being her first language, a language in which she holds a Masters" degree and is her teaching subject. A number of studies have found that language leads to challenges for OTTs (Guo & Singh, 2009;Mawhinney and Xu, 1997;Schmidt, 2010;Sharplin, 2009;Subedi, 2008;Walsh, 2008;Walsh, Brigham and Wang, 2011). Ordinarily those challenges are faced by OTTs for whom English is not a first language.…”
Section: Culture Shockmentioning
confidence: 99%
See 1 more Smart Citation